On-station comparative analysis of reproductive and survival performance between Red Maasai, Dorper, and Merino sheep breeds - G. Wanjala; N. Kichamu; P. Strausz; P.K. Astuti; Sz. Kusza (Animal, 2023)
The reproductive performance of ewes and the survivability of lambs to weaning have a critical economic impact on sheep farming worldwide. Further, knowledge of major mortality causes allows an opportunity for improved flock management to evade financial losses. The maximum likelihood estimates for generalised linear mixed models and chi-square test methods were used to examine 971 mating records, 839 and 763 lambs born and weaned (singles or twins) from the Naivasha Sheep and Goats station in Kenya for the years 2011 to 2020 consisting of Dorper, Red Maasai (RedM), and Merino breeds. The RedM (P < 0.05) outperformed Dorper and Merino in weaning rate, whereas reproductive performance between the three breeds was not significantly different (P > 0.05) in litter size and multiple lambings per ewe lambing. On the one hand, Dorper significantly (P < 0.05) outperformed the other two breeds only in weaning weight per lamb born. In addition, among all the major causes of death, pneumonia appeared to be the one to which Dorper breeds were most susceptible (chi-square test, P < 0.05). According to the findings of this study, neither the Dorper nor the Merino sheep breeds were reproductively superior to the RedM in an extensive semi-arid production environment. In addition, Dorper's susceptibility to the leading causes of mortality, particularly pneumonia and sheep pox, were relatively high compared to other breeds and could be a precursor to massive economic losses for Dorper sheep producers. In contrast to the indigenous RedM breed, imported sheep breeds appeared to be more susceptible to major mortality-related under an extensive production system. Therefore, regardless of weaning weight, RedM breed production appears to be a more viable investment for small-scale farmers, particularly in semi-arid regions.